Entre censure politique et domination masculine : représentations des sportives olympiques dans les biopics chinois (1981-2022) - Siyao Lin (Genre & Histoire)
In 2021, concerns about the status of sportswomen in China were once again raised by the case of Peng Shuai, a Chinese tennis player who dared to publicly protest against the alleged sexual assault she suffered at the hands of former Communist leader Zhang Gaoli. Even though the Chinese government regularly promotes a positive image of sportswomen in the media, notably in Olympic biopics, it is important not to equate these films with a genuine feminist movement. By analyzing eight Chinese biopics focused on Olympic athletes, this article will first demonstrate how these biopics, blending fiction and reality, glorify the achievements of Olympic athletes. Secondly, a figurative analysis will highlight the narrative strategies that limit characters to the role of “good daughters of the nation” in international competitions. Finally, a study of athletes from ethnic minorities will provide insight into the multiple power dynamics and the metaphor of the Olympic Games in political propaganda.